Numerical assessment of solar panel with utilizing ferrofluid flow within wavy duct equipped with V-shaped fins - Mohammed A. Tashkandi; Ali Basem; Hussein A.Z. AL-bonsrulah; Lioua Kolsi; Mahmood Shaker Albdeiri; Lotfi Ben Said; Amira M. Hussin (Case Studies in Thermal Engineering)
This research evaluates the performance of a solar panel under the influence of dust deposition and explores methods to enhance its efficiency. The panel's cooling system incorporates a wavy duct design fitted with V-shaped fins, and the working fluid—water—is augmented with nanoparticles to improve heat transfer. Lorentz force is applied in the y-axis direction to regulate the flow of the ferrofluid, a mixture of water and magnetic nanoparticles. The simulation involves modeling various layers of the panel to account for heat conduction, including the heat generated by solar irradiation. The study reports the electrical efficiency (ηPV) and thermal efficiency (ηth) under different operational parameters. The application of a higher Hartmann number (Ha) results in a cooler panel and warmer nanofluid at the outlet. However, the presence of dust significantly diminishes the positive effects of the magnetic field on both efficiency metrics, particularly reducing ηPV by 10.22 %. As the Hartmann number increases, the temperature across the silicon layer decreases, and the uniformity of the isotherms improves by approximately 5.2 %. When the Hartmann number is set to 95, an increase in dust levels leads to a reduction of 25.33 % in ηPV and 9.82 % in ηth. Additionally, the work finds that the impact of the (ϕ) on both ηPV and ηth is significantly greater at a higher inlet velocity (Vin = 0.093), being 3.96 and 2.7 times greater, respectively, compared to a lower velocity (Vin = 0.018).